STUDY OF CLINICAL, SUBCLINICAL AND EVALUATION OUTCOMES OF BILATERAL SCROTO-INGUINAL MICROSURGICAL VARICOCELECTOMY AT CAN THO CENTER GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Background: Varicocele is by far the most commonly performed operation for the treatmentof male infertility. Varicocele is found in approximately 15% of the general population, 35%of men with primary infertility, and 75% to 81% of men with secondary infertility. Methods:A prospective and retrospective clinical descriptive study of 32 patients with varicocele whowere diagnosed and treated by microsurgical varicoceletomy at Can Tho Central GeneralHospital from March 2015 to July 2019. Results: Symtoms: scrotal paint 59,4%, infertility31,3%, scrotal paint and infertility 9,4%. Left scrotal pain 86,4%, both scrotal pain 13,6%.Varicocele grade III 71,9% and grade II 28,1%. Scrotal untrasound detected 75% cases.77,3% complete resolution of pain, 22,7% a partial resolution of pain. Natural pregnancy rate53,8%. There were neither intraoperative nor postoperative complications. Conclusions:Varicocele’s diagnosis depends on clinical. Microsurgical varicoceletomy is a safe, effectiveapproach in treatment scrotal pain and infertility.
Keywords: Varicocele, scrotal pain, male infertility, microsurgical varicoceletomy.